The Physicochemical, Microbiology, and Sensory Characteristics of Kefir Goat Milk with Different Levels of Kefir Grain - Sulmiyati Sulmiyati; N. S. Said; D. U. Fahrodi; R. Malaka; F. Maruddin (Faculty of Animal Science, Bogor Agricultural University, 2019)
Kefir is a fermented milk product. The kefir grain starter consists of lactic acid bacteria and yeast that produce lactic acid and alcohol. The quality of kefir is strongly influenced by the type of milk used, the amount of kefir grain, kefir grain microorganisms, and the incubation period. The characteristics of goat-milk kefir with the addition of different amounts of kefir grain were studied by measuring pH value, ethanol content, and percentage of lactic acid. The experimental design was a completely randomized design (RCD) with three treatments and five replications. The treatments were performed by using different amounts of kefir grains i.e., 2%, 4%, and 6%. Goat-milk kefir was pasteurized at 105oC for 5 minutes, cooled at room temperature (37oC), and then kefir grain was added at different levels and incubated for 12 hours. The results showed that the amounts of kefir grain had a significant effect (p<0.05) on pH value, the percentage of lactic acid, and ethanol content of goat-milk kefir produced. The higher dose of kefir grain had an influence on physicochemical characteristics, microbiology, and sensory of goat-milk kefir. The optimal characteristics of goat-milk kefir were 2% kefir grain with a pH value of 5.40, lactic acid content of 0.14%, and ethanol content of 0.69%. The weight gain of kefir grain was 7.21% and the total of lactic acid bacteria was 1.64x107 CFU/mL. Sensory quality had a white color, kefir scent, a non-acid taste, and like preference. It is concluded that the best goat-milk kefir can be produced by the addition of 2% kefir grain based on physicochemical, microbiological, and sensory characteristics.